2013
DOI: 10.1111/acfi.12049
|View full text |Cite
|
Sign up to set email alerts
|

The impact of the antecedents and consequences of job burnout on junior accountants' turnover intentions: a structural equation modelling approach

Abstract: This paper examines the impact of the antecedents and consequences of job burnout on junior accountants' turnover intentions. A questionnaire was completed by 368 junior accountants working in public accounting firms. Our results suggest that role ambiguity, role conflict and job-related tension are important antecedents for job burnout. Role ambiguity and role conflict initially influence employees' perceived levels of job-related tension, and job-related tension is associated to job burnout, which, in turn, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
106
0
6

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 97 publications
(129 citation statements)
references
References 78 publications
5
106
0
6
Order By: Relevance
“…job satisfaction) than with the other elements. The result from Chong and Monroe (2015) demonstrates that not all dimensions have a significant correlation with job satisfaction, and confirmed that emotional exhaustion is significantly related to higher levels of dissatisfaction.…”
Section: The Relationship Between Emotional Exhaustion and Job Satisfmentioning
confidence: 76%
See 3 more Smart Citations
“…job satisfaction) than with the other elements. The result from Chong and Monroe (2015) demonstrates that not all dimensions have a significant correlation with job satisfaction, and confirmed that emotional exhaustion is significantly related to higher levels of dissatisfaction.…”
Section: The Relationship Between Emotional Exhaustion and Job Satisfmentioning
confidence: 76%
“…This relationship has been evidenced consistently in public accountants (e.g. Fogarty et al 2000;Jones et al 2010;Chong and Monroe 2015). However, most of the behavioral research does not examine the relationship for each dimension of burnout separately.…”
Section: The Relationship Between Emotional Exhaustion and Job Satisfmentioning
confidence: 92%
See 2 more Smart Citations
“…Burn out diminishes mental and physical vigor of experiencing subjects (Eker & Anber, 2008), causes mental and physical fatigue, sleeplessness, and family issues and may also lead to extensive consumption of drugs and liquors (Maslach & Jackson, 1981). Burn out diminishes productivity and efficiency of individuals which in turn affect the levels of their satisfaction with jobs, and commitment with organizations (Chong & Monroe, 2015). A continuous state of being burned out may also result in early retirements or resignations (Spreitzer, et al, 2012).…”
Section: Burnout Turnover Intentions and Workplace Incivilitymentioning
confidence: 99%